Epidemiological profile of hospitalizations related to Crohn's Disease and Ulcerative Colitis in the state of Minas Gerais (Research, Society and Development, 2024)
Crohn's Disease (CD) and Ulcerative Colitis (UC) are Inflammatory Bowel Diseases (IBD), chronic conditions with multiple causes, including genetic, immunological, and environmental factors. In Brazil, there has been an increase in IBD, especially in industrialized areas; however, few studies address the epidemiological profile of these conditions. This study aims to analyze hospitalizations and deaths due to CD and UC. The research used a cross-sectional quantitative methodology with data from DATASUS, analyzing 5,103 hospitalizations for IBD in Minas Gerais between 2014 and 2024. The variables included number of deaths and hospitalizations and hospitalizations by: sex, age group, color/race, type of care, total value, average number of days. There was a predominance of emergency hospitalizations (95%), with a higher incidence in women (56.6%) and brown people (51.9%), concentrated mainly among the age group of 20 to 49 years. The average length of hospital stay was 6.9 days, with peak mortality rates recorded in 2020 and 2023. The discussion highlighted the influence of environmental factors on the progression of IBD. The higher incidence in women may be related to hormonal differences. Cases in young adults indicate an impact on the economically active population. The higher number of cases among brown individuals reflects the demographics of the region. Emergency hospitalizations and their high costs highlight the need for prevention and early diagnosis, while peak mortality rates highlight challenges in clinical management. Identifying the epidemiological profile of these diseases directs efforts to optimize resources and improve quality of life, promoting a more effective approach to managing these conditions.